DESIGNING A VACCINE FOR CANCER: A LOOK INTO DENDRITIC CELL CANCER VACCINE: New era of dendritic cell cancer vaccine - PRAVEEN KUMAR VEMURI; ANKITHA KUNTA; RISHITHA CHALLAGULLA; ELIZABETH ANWITHA JOSE; BODIGA, VIJAYA LAKSHMI BODIGA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The fundamental premise behind clinical approaches for dendritic cell-mediated immunization in cancer is that the limiting defect in natural antitumor immunity is at the level of antigen presentation. In contrast to vaccines for the prevention of infections, cancer vaccines are administered in a therapeutic mode, to eradicate antigen-bearing tumor cells already present in the host. Over the decades, the identification of antigens that can serve as targets for immune effectors has resulted in a profusion of strategies for activating tumor antigen-specific immune responses. Therapeutic vaccines, unlike prophylactic vaccines for the prevention of infections, all share some basic attributes, the presence of target antigens, and a method for delivering the antigen into the antigen-presentation machinery in conjunction with other molecules required to provide T-and/or B-cell activation.